Incentive structure and efficiency in the Kenyan civil service - Damiano Kulundu Manda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Kenya's civil service expanded rapidly after independence, becoming by far the largest in East Africa. Following economic decline since the 1980s, however, it became difficult for the government to sustain a large and inefficient public sector. To raise efficiency, extensive civil service reforms and changes in its incentive structure were necessary to reflect the government's new priorities. The main factors affecting performance in the civil service include low salaries and allowances for the civil servants, lack of equipment and office space, poor compensation, absence of a career-development structure, and poor delegation. This paper examines factors affecting efficiency in the Kenyan civil service with emphasis on incentive structures, ranging from wage emoluments, training and promotion procedures and sanctions against poor performance. Several incentive realignments for improving efficiency in the civil service emerge. First, salaries and other emoluments of the civil service should be improved to a level deemed conducive to increasing morale and productivity and maintained to preserve it in real terms via periodic reviews and in line with macroeconomic developments. The existing huge gaps between government and private sector wages for highly skilled workers should be narrowed to enable the government to retain its productive staff. Currently, retrenchments are used to reduce the size of the civil service and to improve productivity, but the government has been too slow in improving its working conditions so as to realise positive impacts of a smaller and flexible civil service. Second, the civil service in Kenya needs to adopt modern management techniques such as performance evaluation, career planning, utilization and effective delegation to enable it achieve efficiency gains in service delivery. In addition, job descriptions and evaluations of job performance should be integrated to the professionalization of the civil service to engender meritocracy in appraisal of individual staff performance. Finally, improved performance by the civil servants with adequate and well-maintained office infrastructure requires an increase in the proportion of government expenditure on equipment and general maintenance. – incentives ; civil service ; Kenya
Keywords: J45; 330; Öffentlicher Dienst; Leistungsanreiz; Kenia